Pro-197-Ser Mutation in ALS and High-Level GST Activities: Multiple Resistance to ALS and ACCase Inhibitors in Beckmannia syzigachne - Wang, Jingjing; Chen, Jingchao; Li, Xiangju; Li, Dan; Li, Zheng; Cui, Hailan (Frontiers in Plant Science, 2020)
American sloughgrass (Beckmannia syzigachne Steud.) is one of the most troublesome weeds infesting wheat and canola fields in China. Some biotypes cannot be controlled, either by acetolactate synthase (ALS) or acetyl coenzyme A carboxylase (ACCase) inhibitors. Which are the main herbicides for controlling this weed. However, very few studies have investigated multiple resistance mechanism in B. syzigachne. In this study, a B. syzigachne biotype with a high resistance to ALS inhibitors we have reported was also showed relatively lower resistance to ACCase inhibitors, with a resistance index around 7. RNA-Seq analysis was used to investigate the factors responsible for multiple resistance, and 60,108 unigenes were assembled by de novo transcriptome assembly and then annotated across eight databases. A Pro-197-Ser mutation was identified in the ALS gene by SNPs analysis and validated by PCR, while, no mutation was identified in the ACCase gene. Nineteen candidate metabolic genes were screened and their overexpression was confirmed by qPCR. The expression of GST-T3 and GST-U6 in resistant plants ranged from 7.5 to 109.4-folds than that in susceptible ones at different times after two kinds of herbicide treatment. In addition, GST activities in resistant plants were 3.0-5.0 times higher than that in susceptible plants. Other novel resistance factors also showed high correlation with multiple resistance which included four genes encoding disease resistance proteins, a transcription factor (MYC3), and one gene conferring blight resistance. In this research, a B. syzigachne biotype was confirmed to have evolved multiple resistance to ACCase and ALS inhibitors. The Pro-197-Ser mutation in ALS gene and high-level GST activities were confirmed responsible for the multiple resistance. Characterized disease-resistance proteins, transcription factor, and blight-resistance proteins may play an essential role in these multiple herbicide resistance.